Tecnicas, materiales y metodos utilizados en la evaluacion de frijol por su reaccion a las enfermedades - Pastor Corrales, Marcial A. (United Nations Development Programme, 1985)
The methodology used for the evaluation of bean germplasm for its reaction to diseases is described. Techniques for the isolation, conservation, inoculum increment, and plant inoculation are included for the pathogens Uromyces phaseoli, Colletotrichum lindemuthianum, Isariopsis griseola, Sclerotium rolfsii, Rhizoctonia solani, Fusarium sp., Xanthomonas campestris pv. phaseoli, and Pseudomonas syringae pv. phaseolicola. (CIAT)